Genetic Diversity and Spatial Genetic Structure in Isolated Scots Pine (Pinus sylvestris L.) Populations Native to Eastern and Southern Carpathians - Șofletea, Nicolae; Mihai, Georgeta; Ciocirlan, Elena; Curtu, Alexandru Lucian (MDPI AG, 2020)
Small, isolated populations are more vulnerable to natural disturbances and loss of genetic diversity. Scots pine, an abundant tree species in the boreal forest of Eurasia, has a scattered natural distribution across Eastern and Southern Carpathian Mountains, where only a few relict populations still exist. We estimated genetic diversity and spatial genetic structure in Scots pine on the basis of microsatellite nuclear markers (nSSR) data. We found a relatively high level of genetic diversity (He = 0.697) within populations and no evidence of recent bottlenecks. Genetic diversity was lower in peat bog populations, as compared to populations that grow on rocky slopes or acidic soils and nutrient-poor sites. Population genetic structure was weak, and genetic discontinuities among populations were detected. Spatial genetic structure (SGS) was observed in nearly all Scots pine populations. The strength of SGS, quantified by Sp statistics, varied greatly among populations, ranging from 0.0011 to 0.0207, with an average of 0.01. Our study highlights that Eastern and Southern Carpathian populations still possess high within-population diversity in spite of the recent fragmentation and reduction of the Scots pine natural distribution range. We discuss the importance of spatial patterns of genetic diversity for developing strategies of conservation and sustainable use of Scots pine genetic resources in the Carpathian region.